2017
DOI: 10.1590/s1679-87592017118206504
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological and biochemical variation of the surf zone diatom asterionellopsis glacialis sensu lato from Santa Catarina, Southern Brazil

Abstract: Patches formed by dense accumulations of diatoms in the surf zone (surf diatoms) are common on sandy beaches with intermediate to dissipative morphodynamic states. Their appearances are correlated with environmental factors such as the passage of cold fronts when onshore winds increase beach hydrodynamics, resuspending epibenthic stocks and accumulating them through the inner surf zone. In Santa Catarina state, Southern Brazil, two beaches are known to have frequent occurrence of accumulations of the surf diat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Saturated and polyunsaturated fatty acids (PUFA) have also been found in some strains of Asterionellopsis glacialis sensu lato (s.l. ), as shown in the work of Viso et al [ 30 ] and Rörig et al [ 29 ]. Various Asterionellopsis strains may also have a different content of lipids and fatty acids related to genetic and chemical diversity of strains [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Saturated and polyunsaturated fatty acids (PUFA) have also been found in some strains of Asterionellopsis glacialis sensu lato (s.l. ), as shown in the work of Viso et al [ 30 ] and Rörig et al [ 29 ]. Various Asterionellopsis strains may also have a different content of lipids and fatty acids related to genetic and chemical diversity of strains [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 63%
“…), as shown in the work of Viso et al [ 30 ] and Rörig et al [ 29 ]. Various Asterionellopsis strains may also have a different content of lipids and fatty acids related to genetic and chemical diversity of strains [ 21 , 29 ]. In addition, Shibl et al [ 31 ] also showed that A. glacialis reprogrammed its transcriptional and metabolic profile in the presence of bacteria, secreting a series of primary metabolites and two unusual metabolites, rosmarinic acid and azelaic acid [ 31 ].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations

Primary Producers

Odebrecht,
de Oliveira da Rocha Franco,
Horta
et al. 2023
Brazilian Marine Biodiversity